Factorial design approach for optimization of floating microspheres of diltiazem hydrochloride - Panwar, Mr. Mangal Singh (Asian Journal of Pharmaceutics (AJP), 2015)
The aim of this study was to perform optimization of floating microspheres of diltiazem hydrochloride for theÂ prolongation of gastric residence time. The microspheres were prepared by a nonaqueous solvent evaporation methodÂ using polycarbonate. A full factorial design was applied to optimize the formulation. Preliminary studies revealed that theÂ concentration of polymer and stirring speed significantly affected the characteristics of floating microspheres.The optimumÂ batch of microsphere exhibited smooth surfaces with good flow and packing properties, prolonged sustained drug release,Â remained buoyant for more than 10 h, high entrapment efficiency up to 97% w/w. Scanning electron microscopy confirmedÂ the hollow structure with particle size in the order of 190 Î¼m. The studies revealed that the increase in concentration ofÂ polycarbonate increased the drug release from the floating microspheres.The results of two third full factorial design revealedÂ that the concentration of polycarbonate (X1) and stirring speed (X2) significantly affected drug entrapment efficiency, percentage release. Key words: Diltiazem hydrochloride, factorial design, floating microspheres, polycarbonate